Illegal wildlife trades and ecological consequences: a case study of the bird market in Fereydunkenar, Iran - Mir Mohamad Tabar, Seyed Ahmad (Deviant behavior, 2024)
Illegal bird hunting in and around the Fereydunkenar International Wetland in Iran has a long history but one with serious ecological consequences. Such hunting has involved the mass killing of critically endangered species - such as Siberian cranes, white-headed ducks, geese, lapwings and wintering raptors - and has caused damage to regional ecosystems. The outcome has been described by conservationists and regional news commentators as a "bird genocide." This study addresses some of the significant problems created by the illegal bird market of Fereydunkenar and explores the reasons for both the actors’ participation and the market’s resilience. The paper draws on original fieldwork - data from qualitative, in-depth interviews with 21 participants actively involved in this bird market. Actors provided various justifications and explanations for their activities, such as food and income, the ineffectiveness of formal controls alongside the supportiveness of informal social norms, and the ability to create an enterprise and attract capital based on simple commodification of nature. The case study illuminates how a traditional practice and a narrowly-focused set of behaviors persist despite the impact of related cascade effects causing harm to ecosystems that push some species to the edge of extinction. The paper therefore serves as an interdisciplinary contribution to green criminology and conservation criminology, as well as to ecological sciences, more generally.